Dapagliflozin‐lowered blood glucose reduces respiratory Pseudomonas aeruginosa infection in diabetic mice. (9th March 2017) - Åstrand, Annika; Wingren, Cecilia; Benjamin, Audra; Tregoning, John S; Garnett, James P; Groves, Helen; Gill, Simren; Orogo‐Wenn, Maria; Lundqvist, Anders J; Walters, Dafydd; Smith, David M; Taylor, John D; et al.
Abstract : Background and Purpose: Hyperglycaemia increases glucose concentrations in airway surface liquid and increases the risk of pulmonary Pseudomonas aeruginosa infection. We determined whether reduction of blood and airway glucose concentrations by the anti‐diabetic drug dapagliflozin could reduce P. aeruginosa growth/survival in the lungs of diabetic mice. Experimental Approach: The effect of dapagliflozin on blood and airway glucose concentration, the inflammatory response and infection were investigated in C57BL/6J (wild type, WT) or leptin receptor‐deficient (db/db) mice, treated orally with dapagliflozin prior to intranasal dosing with LPS or inoculation with P. aeruginosa . Pulmonary glucose transport and fluid absorption were investigated in Wistar rats using the perfused fluid‐filled lung technique. Key Results: Fasting blood, airway glucose and lactate concentrations were elevated in the db/db mouse lung. LPS challenge increased inflammatory cells in bronchoalveolar lavage fluid from WT and db/db mice with and without dapagliflozin treatment. P. aeruginosa colony‐forming units (CFU) were increased in db/db lungs. Pretreatment with dapagliflozin reduced blood and bronchoalveolar lavage glucose concentrations and P. aeruginosa CFU in db/db mice towards those seen in WT. Dapagliflozin had no adverse effects on the inflammatory response in the mouse or pulmonary glucose transport or fluid absorption in the rat lung. Conclusion and Implications: Pharmacological lowering of blood glucose with dapagliflozin effectively reduced P. aeruginosa infection in the lungs of diabetic mice and had no adverse pulmonary effects in the rat. Dapagliflozin has potential to reduce the use, or augment the effect, of antimicrobials in the prevention or treatment of pulmonary infection.